MODERN TRENDS IN THE DEVELOPMENT OF HEALTH PHYSICAL CULTURE - Samolovov, N.A.; Samolovova, N.V.; Semyonova, G.I.; Bespamyatnykh, E.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally prove the effectiveness and safety of using the method of forming a neutral position of the spine in fitness for the abdominal muscles. Methods and structure of the study. The experiment was carried out on the basis of the “Ratiborets” fitness club in Yekaterinburg. It was attended by 14 women aged 30 to 38 years. For the experimental group, a training program was developed that included exercises that strengthen the abdominal muscles by stabilizing the spine in a neutral position. The experiment took place in three stages. The first stage was aimed at the development of static stabilization, the second - dynamic stabilization, the third - integrated stabilization. Results and conclusions. The introduction of training in the work of fitness clubs for the development of static and dynamic stabilization with the control of execution technique strengthens the posture, axial muscles, increases the strength and endurance of the abdominal muscles. Moreover, such training is safe for the spine, since the main task of the method of forming the neutral position of the spine is to maintain the physiological (natural) curves of the spine and distribute the load optimally over all joints, thereby protecting them from injury.